Video-based collaboration to develop language production skills - Sandra Vasconcelos; Ana Balula (Ubiquity Proceedings)
This paper explores the integration of digital technology, particularly the video-based tool Flipgrid, to enhance language learning, focusing on communication competences. Rooted in the Common European Framework of Reference for Languages, the study outlines an innovative activity designed for A1 level German learners, grounded in 3 phases: i) planning, ii) execution, and iii) evaluation and repair. By leveraging the asynchronous nature of Flipgrid discussions, students engage in cross-university collaboration, exposing them to diverse perspectives and fostering a supportive learning environment. Besides fostering collaboration through video-based peer review, the activity aims at reducing anxiety associated with public speaking, preparing students for success in today's interconnected world. Further research may involve content analysis to explore the efficacy of video-based peer review in language learning. Through continued exploration of innovative approaches to digital language learning, teachers can empower students to become more proficient communicators, equipped with essential skills for success in today's globalized society.